EFEK HIPOGLIKEMIK EKSTRAK ETANOL UMBI KETELA RAMBAT (Ipomoea batatas P) (EEUKR) PADA MENCIT SWISS YANG DIINDUKSI ALOKSAN - Akrom, Akrom; D, Harjanti P; T, Armansyah (Universitas Ahmad Dahlan, 2014)
Sweet potatos rood contain lots of beta-carotene, polyphenols and flavonoids. Alloxan provenpancreatic cell damage through oxidative stress mechanisms. The compound beta-carotene,polyphenols and flavonoids are thought to antioxidative and cytoprotective, inhibit cell damage causedby alloxan exposure. This study aimed to determine the effect of ethanolic extract of sweet potatos(Ipomoea batatas P) (EEUKR) on blood glucose levels and pancreatic histopathology on alloxaninducedSwiss mice. Used 15 test animals, Swiss mice, with an average weight of 20-30 grams. Testanimals were divided into 5 groups, with each group consisting of 3 mice. Group I was the negativecontrol group who were given distilled water (akua group), and group II, III, IV and V are thetreatment group were given ethanolic extract of sweet potatos rood (EEUKR) at a dose of 2.5, 7.5,22.5 and 67.5 mg/KgBW/day orally for 10 days, 7 days before and 3 days after the alloxan induced.Alloxan induction performed on the 7th day intraperitoneally at a dose of 120 mg/kgBW. Examinationof blood glucose levels conducted on 4th and day 10th day of treatment. On the 10th day of the testanimals were sacrificed for isolated pancreas and histopathologic examination. Analysis of varianceconducted to determine the significance difference in average blood glucose levels between groupsduring the test and ANOVA followed by LSD test at 95% confidence level. Pancreatic histopathologydata were analyzed qualitatively. The results showed that the EEUKR dose of 22.5 and 67.5mg/kgBW/day had the effect of hypoglycemia in Swiss mice. Blood glucose levels of Swiss micebefore alloxan induced in treatment group with EEUKR dose of 67,5 mg/Kg BW were lower thanblood glucose levels of akua groups, statistically significant (p <0,05). Blood glucose levels of alloxaninduced swiss mice of treatment groups with EEUKR dose of 22.5 and 67.5 mg/KgBW were lowerthan blood glucose level of akua group and statistically significant (p <0.05). The percentage ofpancreatic necrosis of alloxan-induced Swiss mice of treatment groups with EEUKR dose of 22.5 and67.5 mg/kg BW were lower than the percentage of necrosis of akua group. Based on these results itcan be concluded that the EEUKR doses of 22.5 and 67.5 mg/KgBW are found to be hypoglycemic inSwiss mice both before and after alloxan induced. The EEUR also shown to decrease the incidence ofpancreatic necrosis in alloxan-induced Swiss mice.